THE INFLUENCE OF DISTILATION TIME, POWDER SIZE, ON THE CINAMYLALDEHYDE CONTENT AND VOLATILE OIL Cinnamomum burmanii Nees ex. Bl. BARK - Lisawati, Yovita; Sulianti, Sri Budi; ., Chairul (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
The content of volatile oil in samples depends on the harvest time, distilation method, sample powder size, and location of sample cultured. The aim of this study was to investigate the influences of interval time of distillation and mesh size of bark powder, upon the concentration of major component (cinamylaldehyde). The distillate was collected with various interval times 1, 2, 3 and 4 hours and it was counted after the first drop of distillate. The mesh size of bark powder (4, 8 and 20 mesh) was set after the interval time of distillation had been studied. The major component was analysed using Gas Chromatography (GC). The results showed that the interval time of distillation at the second hour gave the highest volatile oil and cinamylaldehyde contents in the relative prosentage 0.19 % and 29.36 % respectively, compared with the first hour distilate, (0.16 %, 24.88 %), third hours distilate (0.14 %, 23.29 %) and fourth distilate (0.08 %, 17.65 %). The powder size of bark (8 mesh) gave the highest volatile oil and cinamylaldehyde contents (0.22 %, 32.81 %), compared to powder size of 4 mesh( 0.17 %, 20.45 %) and 20 mesh (0.19 %, 21.32 %). The results is still lower than standard of cinnamon oil, (cinamylaldehyde content 60 %). The lowering cinamylaldehyde content could be caused by low quality of material, collected from marketing method, early harvesting time, and storing for long.time.Key words: C. burmanii, bark, distilation time, cinamylaldehide